ANALISIS KESALAHAN EJAAN PADA SURAT DINAS PESERTA DIDIK KELAS VII SMP NU 06 KEDUNGSUREN KALIWUNGU SELATAN KENDAL TAHUN PELAJARAN 2018/2019 - Diah Hesti Safitri; Nanik Setyawati; Ahmad Rifai (Universitas Ngudi Waluyo, 2020)
Application of the Contextual Teaching and Learning Model in Learning to WritePersuasive Texts in Students of Class VIII of SMP Negeri 1 Tunjungan in the 2018/2019Academic Year. Thesis. Faculty of Language and Arts Education, University of PGRISemarang. Advisor 1 Dr. Asropah, M.Pd. and Pembing II Drs. Murywantobroto, M.Hum.July 2019. The purpose of this study was to describe the application of the ContextualTeaching and Learning (CTL) model in learning to write persuasive texts in grade VIIIstudents of SMP Negeri 1 Tunjungan in the 2018/2019 academic year. Data collectionmethods used in this study were technical tests and non-tests. The test technique is in theform of writing persuasion texts in writing according to the theme, structure, languagerules and correlations between paragraphs. Whereas the nontest technique is in the formof an observation sheet of learning activities of teachers and students and questionnaires.The approach used is descriptive qualitative. The population in this study were all studentsof class VIII. The sample in this study was class VIII B, amounting to 31 participants.The technique of presenting the results of the data analysis was done qualitatively byanalyzing the application of the Contextual Teaching and Learning model in learning towrite persuasive texts to students of class VIII of SMP Negeri 1 Tunjungan. The resultsobtained in learning to write persuasion text using the Contextual teaching and Learningmodel can be applied in learning to write persuasion text in class VIII of SMP Negeri1 Tunjungan in the 2018/2019 school year. The ability of students to write persuasiontexts gets good grades. Students can write persuasion texts by analogizing the themes thathave been determined. Thus, students can pour ideas freely. This can be seen from theaverage value of students reaching 88, the highest value of 100, and the lowest value of76.Keywords: application, Contextual Teaaching and Learning model, writing persuasiontexts